Drying-Rewetting and Flooding Impact Denitrifier Activity Rather than Community Structure in a Moderately Acidic Fen - Palmer, Katharina; Köpp, Julia; Gebauer, Gerhard; Horn, Marcus A. (Frontiers in Microbiology, 2016)
Wetlands represent sources or sinks of the greenhouse gas nitrous oxide (N2O). The acidic fen Schlöppnerbrunnen emits denitrification derived N2O and is also capable of N2O consumption. Global warming is predicted to cause more extreme weather events in future years, including prolonged drought periods as well as heavy rainfall events which may result in flooding. Thus, the effect of prolonged drought and flooding events on the abundance, community composition and activity of fen denitrifiers were investigated in manipulation experiments. The water table in the fen was experimentally lowered for 8 weeks in 2008 and raised for 4 months in 2009 on 3 treatment plots, while 3 plots were left untreated and served as controls. In situ N2O fluxes were rather unaffected by the drought treatment and were marginally increased by the flooding treatment. Samples were taken before and after treatments in both years. The structural gene markers narG and nosZ were used to assess possible changes in the nitrate reducer and denitrifier community to water table manipulations. Detected copy numbers of narG and nosZ were essentially unaffected by the experimental drought and flooding. Terminal restriction fragment length polymorphism (TRFLP) patterns of narG and nosZ were similar before and after experimental drought or experimental flooding, indicating a stable nitrate reducer and denitrifier community in the fen. However, certain TRFs of narG and nosZ transcripts responded to experimental drought or flooding. Nitrate-dependent Michaelis-Menten kinetics were assessed in anoxic microcosms with peat samples taken before and 8 weeks after the onset of experimental flooding. Maximal reaction velocities vmax were higher after than before flooding in samples from treament but not in those from control plots taken at the same time. The ratio of N2O to N2O+N2 was lower in soil from treatment plots after flooding than in soil from control plots, suggesting mitigation of N2O emissions by increased N2O-reduction rates after flooding. N2O was consumed to subatmospheric levels in all microcosms after flooding. The collective data indicate that water table manipulations had only minor effects on in situ N2O fluxes, denitrifier abundance, and denitrifier community composition of the acidic fen, while active subpopulations